Between the wires : the Janowska camp and the Holocaust in Lviv - Beorn, Waitman Wade, 1977- ([University of Nebraska Press], 2024)
Between the Wires tells for the first time the history of Janowska, in Lviv, Ukraine, one of the deadliest concentration camps in the Holocaust, by bringing together never-before-seen evidence and painstakingly detailed research from archives in seven countries and in as many languages.